English Inflectional Morpheme Accuracy in Indonesian EFL Students - Sipri Hanus Tewarat; Zia Hisni Mubarak; Afriana Afriana (eScience Humanity Journal, 2025)
The study focused on how accurately fourth-semester English Literature students at Putera Batam University used eight types of English inflectional morphemes in their academic writing. Employing a descriptive qualitative approach complemented with simple statistical descriptions, the study reviewed students’ written assignments along with questionnaire data to determine their level of accuracy, the most frequent error patterns, and the factors contributing to incorrect forms. To assess accuracy, the researchers adopted Brown’s (1973) calculation and applied an 80% benchmark to classify whether a morpheme had been sufficiently acquired. The analysis revealed that only three morphemes—the present participle (-ing), the superlative (-est), and the simple past (-ed)—met or exceeded the expected mastery level. In contrast, several others, including the comparative (-er), the past participle (-ed/-en), the possessive (’s), and the third-person singular (-s), fell well below the threshold, suggesting that students had not yet mastered them. Further examination showed that omission was the error type that occurred most frequently, while misformation and addition followed as secondary patterns. The inaccuracies were largely attributed to the influence of Bahasa Indonesia as the learners’ first language and to internal developmental factors such as overgeneralization and partial understanding of grammatical rules. Overall, the findings point to persistent difficulties Indonesian EFL learners encounter when dealing with English inflectional morphology and emphasize the importance of more focused grammar instruction within academic writing courses